RESPONSE SOME OF BLACK LOCAL RICE SEEDS WEST KALIMANTAN DROUGHT STRESS ON THE GERMINATION PHASE - LINA, LINA; PALUPI, TANTRI; ANGGOROWATI, DINI (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRACTIn West Kalimantan there are several types of local black rice varieties, among others; Beliah, Gula, Itam, Tabah, Ukah, Poe Arank, Senakin, Sekadau 1, Sekadau 2, and two varieties of comparison: Ciherang, and Inpago 8, which have been cultivated for generations. Local black rice is very popular by the community because it is easy in the implementation of cultivation, cheap production costs, and rice product can be made into various types of food, in which the results are better than white rice. The objective is to find out the response of 9 types of local black seeds in West Kalimantan to the drought stress in the germination phase. This research was Designed in a Completely Randomized Design (CRD) method. The observed parameters were; vigor index (%), germination (%), growth rate (% / etmal), plumule length (cm), root length (cm) and normal germination weight (g). Polyethylene Glycol (PEG 6000) concentration of 20% used as a treatment to drought stress (mg). The results showed that the seeds of local black rice rice from West Kalimantan namely Beliah, Gula, Itam, Senakin, Sekadau 1, Sekadau 2, Ukah, Poe arank treaded applied with PEG 6000 solution as drought stress simulation showed good response when viewed from benchmark vigor seed (vigor index, and growing speed). While black seeds of Tabah showed a bad response (20% vigor index, growth rate 13.03% / etmal, 4.09 cm long plumule). Keywords: rice seed, PEG 6000, seed response, salinity